Sadaqah-Based Crowdfunding Model for Microfinancing and Health Care - Lutfi, M. A.; Ismail, M. A. (Universiti Sains Islam Malaysia, 2024)
The rapid development of payment technology and internet network throughout the world make crowdfunding to be used widely as mechanism for funding. Generally, the crowdfunding adapts the concept of microfinancing and crowdsourcing, but it has unique characteristics of its own. This present paper is aimed to investigate the potentials crowdfunding and proposes a crowdfunding model which is complies with Shariah using permissible contracts namely sadaqah and qard al-hasan. The present study was conducted using qualitative method through library research. The study found that the crowdfunding has been employed in various models; donation-based and investment-based models. It was also found that it is permissible for the crowdfunding to be incorporated with the Shariah complied contract of sadaqah in order to mobilize the fund from the community. Therefore, this study proposed a sadaqah-based crowdfunding model. The model has main roles to provide microfinancing for entrepreneurial projects and set up health care fund for the treatment costs of the needy.